Laying down the nets in open sea - Mumbai Archive Project Team (Jio Institute, 2024)
After waiting a few hours, depending on the weather and other factors, the nets are hauled, and boats return by noon. Larger trawlers, which have bigger nets, remain at sea for several days and leave their nets in the sea overnight.